Review of sliding mode based control techniques for control system applications - Gambhire, S. J.; Kishore, D. Ravi; Londhe, P. S.; Pawar, S. N. (International journal of dynamics and control, 2021)
In recent development in the control area, advanced control schemes are well established for the systems under the influence of parametric uncertainties due to modelling error, nonlinearities, and the external disturbances. Among the different robust control schemes sliding mode control (SMC) has made attention for the control engineer due to its merits. SMC has grown rapidly as a control in comparison with other robust control strategies due to its distinguish features like insensitive to matched uncertainties, reduced order sliding mode equations, zero error convergence of closed loop system and it offers a nonlinear control. The objective of this paper is to present the literature review of SMC development in an era of control technology. The development of SMC based technique with integration of intelligent control in the field of control engineering has been surveyed by considering numerous applications.